PENGARUH KEPRIBADIAN DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA PEGAWAI DI KANTOR BAPENDA TORAJA UTARA - Rantika Madao; Jemi Pabisangan Tahirs; Dwibin Kannapadang (JURNAL ILMIAH EDUNOMIKA, 2026)
This study aims to determine the influence of personality and work motivation on employee job satisfaction at the North Toraja Bapenda office.The research uses a quantitative approach with a survey method. The research population is employees of BAPENDA North Toraja, with a sample of 65 respondents determined using saturated sampling techniques. Data collection was carried out through the distribution of questionnaires using the Likert scale. The results of the study showed that partially personality had a positive and significant effect on job satisfaction with a significance value of 0.046 < 0.05 and a t-value of 2.521 > t table of 1.999. Work motivation also had a positive and significant effect on job satisfaction with a significance value of 0.046 < 0.05 and a t-value of 2.039 > t table of 1.999. Simultaneously, personality and work motivation had a positive and significant effect on job satisfaction with an F value of 9.844 > F table 3.15 and a significance value of 0.000, 0.05. The determination coefficient value (R2) of 0.241 showed that personality and work motivation were able to explain 24.1% of the variation in job satisfaction, while the remaining 75.9% was influenced by other factors outside the study